2020
DOI: 10.21203/rs.3.rs-25191/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

OSCE 3D: a virtual clinical skills assessment tool for coronavirus pandemic times

Abstract: Background : In pandemic times where the “lockdown strategy” has been adopted, the use of innovations using technological resources such as the creation of instruments that can replace traditional teaching-learning methods in the training of health professionals is essential. The aim of this study was to develop and evaluate the usability of a realistic interactive simulation computer system using three-dimensional imaging technology and virtual reality with free-access computational tools available on the web… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Self‐regulated learning has become more important in online learning environments, as distance learning requires students' agency and ownership of their learning (Çebi & Güyer, 2020). The reviewed studies revealed that the levels of self‐regulated learning in online environments were higher than (Faria et al., 2021; Rodríguez Fernández et al., 2021) or similar to that of face‐to‐face classes (Domínguez‐Torres et al., 2021). However, some students reported difficulties in self‐regulated learning (Molina Gutiérrez et al., 2021).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Self‐regulated learning has become more important in online learning environments, as distance learning requires students' agency and ownership of their learning (Çebi & Güyer, 2020). The reviewed studies revealed that the levels of self‐regulated learning in online environments were higher than (Faria et al., 2021; Rodríguez Fernández et al., 2021) or similar to that of face‐to‐face classes (Domínguez‐Torres et al., 2021). However, some students reported difficulties in self‐regulated learning (Molina Gutiérrez et al., 2021).…”
Section: Resultsmentioning
confidence: 97%
“…For example, one study found that students using social media exhibited excellent learning performance (Mendoza‐Lizcano et al, 2020). However, in other studies, students reported having some difficulties in online learning activities (Bazán‐Ramírez et al., 2020), which they needed a considerable amount of training to ensure that their performance was not affected (Faria et al., 2021), indicating that online learning requires more work (Molina Gutiérrez et al., 2021).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Prettyman et al (Prettyman et al, 2018) diseñan un ECOE virtual e indican que requiere recursos tecnológicos mínimos, puede implementarse en un corto período de tiempo, elimina la necesidad de que los estudiantes estén en el campus, siendo efectivo en el aprendizaje y evaluación de las competencias clínicas. Recientemente, Loureiro et al (Faria et al, 2020) han desarrollado un prototipo de bajo costo, utilizando un sistema tridimensional de simulación realística para estaciones de evaluación del ECOE, el cual incluso en la fase de prototipo, ha mostrado buena usabilidad.…”
unclassified